Forming professional mobility of future pedagoges in conditions of pedagogical college - Ruzhytskyi, Valerii (ScienceRise: Pedagogical Education, 2019)
The article is devoted to the issues of professional mobility formation of future primary school teachers. The essence of the concept "professional mobility" is defined, and the content analysis of the concept in scientific sources is conducted. We consider professional mobility of students as an integrative quality of the individual which allows: to get a qualitative solution of professional tasks in the established timeframes using the most effective technologies of future professional activity; to develop independently new technologies of professional activity on the speciality or related speciality, if necessary; to be active and communicatively competent in different situations. The pedagogical conditions of the group of pedagogical factors of future teachers’ professional mobility formation in the pedagogical college are considered and the groups of approaches to the process of future teachers’ professional mobility formation are defined as: pedagogical, psychological, psychological and pedagogical, socio-economic. The pedagogical conditions, revealed in the article, are analysed as an integral part of the pedagogical system: they reflect various possibilities that influence the personal and professional aspects of the system, contributing to its successful functioning. The pedagogical conditions for the future teachers’ professional mobility formation in the conditions of the pedagogical college include: the creation of an innovative educational environment in the college, the formation of students’ creative activity, the implementation of the system-integrative organization of training students to the formation of students’ professional mobility on the basis of systemic, synergetic, competence and subjective approaches . The author reveals the structure of future teachers’ professional mobility formation in a pedagogical college. The components of the structure of the future teacher’s professional mobility are described. The criteria, indicators and levels of students’ professional mobility formation in the pedagogical college are defined and described